Towards optimal toe-clearance in synthesizing polycentric prosthetic knee mechanism. Issue 6 (26th April 2022) - Marisami, P.; Venkatachalam, R.
Abstract: Stability at the stance phase and near normal able-bodied swing phase kinematics are essential in designing the prosthetic knee mechanism for transfemoral amputees. Primarily, insufficient mid swing toe clearance results in asymmetrical gait patterns, leading to muscular-skeletal pain and joint degeneration. The present work is focused on synthesizing a polycentric knee mechanism to enhance the toe-clearance at mid-swing for safe level ground walking of amputees in developing countries. Both fixed and moving centrodes of the four-bar knee mechanism are considered in optimal synthesis of the mechanism for achieving able-bodied gait patterns using evolutionary algorithms in mechanism design software tools. The knee stability at heel contact, stabilizing moment at push-off, stable knee flexion range, maximum knee flexion and maximum toe-clearance at mid-swing are the parameters used for comparing the knee design with the existing commercially available designs. The optimized results are then verified experimentally by building a functional prototype using a 3 D printing technique. The designed mechanism executes nominal performance in four parameters and offers enhanced toe-clearance during mid-swing. This is a significant improvement over the existing designs for amputees to navigate comfortably on irregular terrain in developing countries.